A NOVEL VARIANT OF HUWE1 GENE IN A FEMALE INFANT WITH SYNDROME PHENOTYPE AND DEVELOPMENTAL DELAY: A CASE REPORT - Giannikopoulou, Iliana; Stogiannidou, Eleni; Oikonomou , Asimakis; Markou , Paraskevi; Karasmani , Paraskevi; Katerelos, Adamantios (MNJ (Malang Neurology Journal), 2025)
This case report presents a rare and novel variant of HUWE1 gene in a female infant with a syndrome phenotype and significant neurodevelopmental deficits. The HUWE1 gene is known to play a crucial role in the development and function of the nervous system. Mutations in this gene have been associated with Turner-type syndromic intellectual developmental disorder (MRXST), a disorder with variable phenotype. This gene is located in X chromosome, and therefore males are affected. Although there are a few cases of female carriers with abnormal findings, or with milder cognitive abnormalities, there are also female patients with de novo mutations who express the full phenotype. Here we describe the clinical and genetic features of a female infant, born to healthy parents and at birth was noted to have abnormal facial features, hypotonia and brachydactyly. At her second hospitalization it was sent genetic testing of her, which revealed a variant in HUWE1 gene, that had never been described in literature.